The Preferences of Muslim Consumers’ Behaviour on Halal Food based on the Utility Maximization Theory - Hawariyuni, Weni; Krishnan, Sarojani (International Journal of Engineering and Technology, 2018)
Halal is no longer just purely a religious issue. It has involved business and trade globally. Furthermore, halal has become a part of quality assurance as well as a healthy lifestyle to be adopted by people today. Halal products are not haram (prohibited) and are known as Shariâ€™ah products. Halal products will ensure that they are Shariâ€™ah-compliant as they exclude haram ingredients, involve exploitation of labour or environment, and are not harmful to the public. Nowadays, most Muslims are aware of the importance of Halal products as per the rules and regulations prescribed by ALLAH SWT in the Al Qurâ€™an and Hadis. Muslims currently demand halal certified products to avoid haram (prohibited) ingredients present in these products. The halal concept, with reference to food, is very crucial for Muslims as they are very sensitive about the ingredients contained in products. Once halal food are identified, Muslim consumers can maximize their consumption of these halal food. As proposed by the Utility Maximization theory, consumers can maximize their utilities in accordance with their budget constraints. The current paper focuses on Halal food consumed by Muslim consumers based on the Utility Maximization theory.Â The purpose of this paper is to propose the conceptual paper of the utility maximization attained by Muslim consumers in consuming halal food.